Rankings of Online Travel Agents, Channel Pricing, and Consumer Protection - Hunold, Matthias; Kesler, Reinhold; Laitenberger, Ulrich (Marketing Science, 2020)
We investigate whether online travel agents (OTAs) assign hotels worse positions in their search results if these set lower hotel prices elsewhere.